Peran Orang Tua dalam Mengembangkan Komunikasi Interpersonal Anak - Fitria Destri, Asti; Ramdini, Dina; Kansa, Muthia; Lailla, Syaipia; Rustini, Tin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The role of parents in shaping children's communication and emotional skills is an important aspect of their social development. However, research on specific strategies used by parents to create an environment that supports children's interpersonal communication is still limited and less focused on practices that can be applied directly. This study aims to explain how parents can create an environment that is conducive to the development of children's interpersonal communication. Using a qualitative approach and the Narrative Literature Review method, this study reviews related literature through Semantic Scholar. The results of the study indicate that parental support is essential in developing effective communication skills. Parents can support this development by creating a home atmosphere that is open to dialogue, providing positive communication models, and listening attentively to children. The uniqueness of this study lies in its approach that highlights a combination of concrete strategies in the family context to support children's interpersonal communication holistically. The implication is that this study can be a practical guide for parents in strengthening their children's communication skills from an early age.